Masa Pembinaan Pendidikan Islam: Telaah Kritis Pendidikan Rasulullah SAW Pada Periode Makkah - Mahfud Ifendi (STAI Sangatta Kutai Timur, 2020)
Abstract Since Islam was born, when the Prophet Muhammad SAW was appointed as an Apostle, then from that moment the Prophet taught Islamic education to his followers. In his journey, of course there were many things that hindered him because indeed what the Prophet Muhammad was doing was very contrary to what most people had done at that time. This article aims to describe and analyze the stages of education Carrie out by the Prophet Muhammad, educational materials and educational institutions that existed during the period during the Prophet in Mecca. Through a qualitative descriptive study approach (library research), the results that can be concluded are: First, there were 3 stages of education Carrie out by the Prophet Muhammad in the Mecca period, namely secretly, openly and publicly. Second, the Islamic education material taught is related to the teachings of tauhid, al-Qur'an and morals. The teaching sofa tawhid became the target of the Prophet for the first time at that time because the Prophet was on a mission for the first time so that he wanted to foster and clean the belief of the Arabs from ignorance that had long worshiped statues oridols (paganism), changed and turned to worship only Allah SWT. In addition to the teachings of tauhid, the Prophet also taught the Qur'an as a guide for life in navigating thelives of mankind both in this world and in the hereafter. The Prophet also taught how to have good morals to Allah SWT, humans and the universe to his friends. Third, the educational institutions used by theProphet Muhammad are the homes of friends of Arqam bin Abi Arqam and around the Grand Mosque in Aqabah to carry out the process of education and preaching to his followers. Of course what is meant by educational institutions here is not like educational institutions today which have experienced changes and advancements in them. What the Apostledidat Dar al-Arqam was very simple because it was indeed a small house of a friend who was suddenly used as an educational institution and for the first time the Prophet delivered Islamic education material to his friends. In general, the Islamic education carried out by theProphet Muhammad in Mecca is a prototype that aimstofoster Muslim personalities to become cadres who are faithful and devoted to Allah SWT, are strong, persistent, patient, intelligent, have noble character to be prepared to be good Muslims. Abstrak Sejak Islam lahir, ketika Nabi Muhammad SAW diangkat menjadi seorang Rasul, maka mulai saat itulah Nabi mengajarkan pendidikan Islam kepada para pengikutnya. Dalam perjalanannya tentu banyak hal yang merintanginya karena memang apa yang dilakukan oleh Rasulullah SAW ini sangat bertentangan dengan apa yang telah dilakukan kebanyakan orang pada saat itu. Dalam artikel ini bertujuan untuk mendeskripsikan serta menganalisis tentang tahapan pendidikan yang dilakukan oleh Rasulullah SAW, materi pendidikan serta lembaga pendidikan yang ada pada periode selama Rasul di Makkah. Melalui pendekatan studi deskriptif kualitatif (libraryresearch), hasil yang dapat disimpulkan adalah Pertama, ada 3 tahapan pendidikan yang dilakukan oleh Rasulullah SAW periode Makkah ini yakni secara sembunyi-sembunyi, terang-terangan dan seruan umum. Kedua, materi pendidikan Islam yang diajarkan adalah berkaitan dengan ajaran tauhid, al-Qur’an dan akhlak. Ajaran tauhid menjadi sasaran Rasul pertama kalinya saat itu karena memang Rasul dalam misi dakwah yang pertama kalinya sehingga beliau ingin membina dan membersihkan keyakinan bangsa Arab dari kejahilan yang telah lama menyembah patung atau berhala (paganisme), berubah dan beralih untuk menyembah hanya kepada Allah SWT. Selaian ajaran tauhid, Rasul juga mengajarkan al-Qur’an sebagai pedoman hidup dalam mengarungi kehidupan umat manusia baik di dunia maupun di akhirat kelak. Rasul juga mengajarkan bagaimana cara berakhlak yang baik kepada Allah SWT, manusia dan alam semesta kepada para sahabat. Ketiga, lembaga pendidikan yang digunakan oleh Rasulullah SAW adalah rumah sahabat Arqam bin Abi Arqam dan di sekitar Masjidil Haram, di Aqabah untuk melaksanakan proses pendidikan dan dakwah kepada para pengikutnya.Tentu yang dimaksud lembaga pendidikan di sini tidaklah seperti lembaga pendidikan dewasa ini yang telah mengalami perubahan dan kemajuan di dalamnya. Apa yang dilakukan oleh Rasul di Dar al-Arqam ini sangat sederhana sekali karena memang merupakan sebuah rumah kecil dari seorang sahabat yang kemudian dijadikan sebagai lembaga pendidikan secara mendadak dan untuk pertama kalinya Rasul dalam menyampaikan materi pendidikan Islam kepada para sahabat. Secara umum, Pendidikan Islam yang dilakukan Rasulullah SAW di Makkah merupakan prototype yang bertujuan untuk membina pribadi muslim agar menjadi kader yang beriman dan bertaqwa kepada Allah SWT, berjiwa kuat, gigih, sabar, cerdas, berakhlak mulia untuk dipersiapkan menjadi muslim yang baik.